Motivation of seniors to learn at the Universities of the Third Age - Daniela Nováková; Jitka Lorenzová (Sociální Pedagogika, 2020)
The study presents the results of a survey examining the motivation of the seniors to receive lifelong learning in university courses. The sample was basedon 150 participants who take these courses in the fields of medicine, the natural sciences and humanities. It was found that the main motive for entering these studies was the desire to further learn a new education skills, followed by the need to actively spend leisure time. The motive of establishing new relationships with peers of similar interests was not significant. The motives were not influenced by the gender, age or education of respondents. A certain relationship has only been proved between theprofessional focus of study and motivation, where the desire to learn a new education skills was slightly more prevalent among students in the fields of medicine and the humanities. The investigation confirmed the importance of the development of internal motivation and pointed to a connection between interest studies and improving the quality of life of seniors.